Implikasi Over Kapasitas di Lembaga Pemasyarakatan Kelas IIA Samarinda Ditinjau dari Konsep Penologi (International Forum of Researchers and Lecturers, 2025)
This study aims to identify, describe, analyze, know and understand the impact and fulfillment of the rights of prisoners against overcapacity in Class II A Samarinda Penitentiary based on the Penology perspective. By using a social legal research approach and a normative legal approach. The data source collection technique uses primary legal data, secondary legal data and tertiary legal data related to the problems studied. The results of the study indicate that first, the impact of overcapacity of Class II A Samarinda Penitentiary on the rights of prisoners reviewed from the Penology concept is the increasing risk of violations containing criminal elements, causing new suffering, sanitation and unhealthy lifestyles. Second, the ideal effort to fulfill the rights of prisoners against overcapacity in Class II A Samarinda Penitentiary is to take preventive measures, namely by approaching inmates in the dormitory and repressive measures, namely imposing disciplinary penalties according to the type of violation committed.